Multi-Technique Approach to Enhance the Properties of Fine Recycled Aggregate Concrete - Amadi, I. G.; Beushausen, H.; Alexander, M.G. (Frontiers in Materials, 2022)
This study investigates the properties of fine recycled aggregates (FRA) with a view to gaining insight on the performance of FRA and how to enhance its properties for structural concrete applications. To enhance the properties of FRA concrete, the study explored several approaches including mixing; curing; systematic screening of FRA particles less than 1.18 mm to reduce the adhered cement paste content and subsequently, the overall porosity of FRA; and the use of fly ash as 30% cement replacement to modify the microstructure of FRA concrete. To test these approaches, two series of concrete mixes were prepared with 0.45 and 0.55 w/b ratio, with FRA replacing natural sand at 0, 25 and 50% by weight, and tests were carried out after 3, 28 and 180 days of curing. Results show the combination of ACP reduction and fly ash treatment significantly enhanced, especially at 180 days, the compressive strength and elastic modulus of FRA concrete through microstructure modification and pozzolanic reactions.